ANALISIS POTENSI DAN KESESUAIAN RENCANA PENGELOLAAN KAWASAN KESATUAN PENGELOLAAN HUTAN SUMBA TIMUR - Nixon Rammang (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2019)
Research results from the 2015 SMERU Poverty Map show that villages located around the area and within forest areas managed by the East Sumba forest management unit tend to be still below the poverty line. To meet the increasingly high needs of life, some people, especially those living around forest areas, have taken over forest areas. The research was conducted in the East Sumba forest management unit forest area. The study was conducted from July to December 2017. In general, all of the East Sumba forest management unit management areas can be reached via land access that has been previously available, both in the form of asphalt roads as well as dirt roads and footpaths. Every village and sub-district in East Sumba Regency as a whole has been connected via land access. Land cover in the East Sumba forest management unit area is dominated by grasslands/savanna (about 55.5% of the total area). Other land cover in a row based on the proportion to the total area of ​​forest management unit is, secondary dry land forest, primary dry land forest, secondary mangrove forest, agricultural area, open land and primary mangrove forest. forest management unit East Sumba based on the results of the analysis has an area of ​​119,879.07 Ha. The East Sumba forest management unit area is broadly categorized into three main parts, namely: Protected Forest category covering an area of ​​73,376.13 Ha (61.2 %), Production Forest category covering 25,418.2 Ha (21.2% ), and the category of Limited Production Forest covering an area of ​​19,084.74 Ha (15.9%). The East Sumba forest management unit management area is dominated by protected forest so that this forest management unit is actually managed as a protected forest management unit. The ecotourism potential that exists in the East Sumba forest management unit management area spreads in several sub-districts, including waterfall tourism, marine tourism and traditional villages. The types of plants that can be developed in the East Sumba forest management unit area are Albizia chinensis, Mahogany. Meanwhile, the type that can be used in the East Sumba forest management unit area is Schleichera oleosa